2015
DOI: 10.1111/jnc.13154
|View full text |Cite
|
Sign up to set email alerts
|

Lack of TNF‐alpha receptor type 2 protects motor neurons in a cellular model of amyotrophic lateral sclerosis and in mutant SOD1 mice but does not affect disease progression

Abstract: Changes in the homeostasis of tumor necrosis factor a (TNFa) have been demonstrated in patients and experimental models of amyotrophic lateral sclerosis (ALS). However, the contribution of TNFa to the development of ALS is still debated. TNFa is expressed by glia and neurons and acts through the membrane receptors TNFR1 and TNFR2, which may have opposite effects in neurodegeneration. We investigated the role of TNFa and its receptors in the selective motor neuron death in ALS in vitro and in vivo. TNFR2 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 48 publications
2
51
0
Order By: Relevance
“…We previously reported that SOD1 G93A expression in both astrocytes and motor neurons determines selective motor neuron death under co-culture conditions 23 . In agreement with previous findings, there were significantly fewer large motor neurons in the AST G93A NEU G93A compared to the AST NTG NEU NTG co-cultures grown for six days in vitro (DIV) after neuron plating, while the number of total spinal neurons remained unchanged (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously reported that SOD1 G93A expression in both astrocytes and motor neurons determines selective motor neuron death under co-culture conditions 23 . In agreement with previous findings, there were significantly fewer large motor neurons in the AST G93A NEU G93A compared to the AST NTG NEU NTG co-cultures grown for six days in vitro (DIV) after neuron plating, while the number of total spinal neurons remained unchanged (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The mice were bred and maintained in a specific-pathogen-free environment. We used NTG and SOD1 G93A mice originally purchased from Jackson Laboratories (B6SJL-Tg-SOD1-G93A-1Gur) and maintained on a C57BL/6JOlaHsd (Harlan) genetic background at the IRFMN 23 . The genotype of the embryos was determined by PCR analysis of DNA extracted from tissue biopsies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, genetic ablation of TNFα had no effect on motor neuron degeneration in ALS-linked mutant hSOD1 mouse models [133]. In addition, deletion of TNFR2 in hSOD1 G93A mice partially protects motor neurons but does not improve motor deficits or survival [134]. Moreover, TNFR1 deletion accelerates motor neuron degeneration and disease progression in the same model, an effect attributed to the disruption of the astrocytic TNFR1-GDNF axis [135].…”
Section: Pathways Involved In Astrocyte-mediated Motor Neuron Toximentioning
confidence: 99%